Insect dome receptor directly recognizes viral envelopes to activate JAK/STAT signaling and induce conserved antiviral viperin expression - Chen, Siyu; Tang, Yupeng; Zhang, Chunyu; Li, You; Jia, Dongsheng; Wei, Taiyun (Cell reports (Cambridge), 2025)
Insect Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway plays a crucial role in antiviral defense, yet how arboviruses activate this pathway remains unclear. Here, we reveal that outer capsid protein of a double-stranded RNA (dsRNA) arbovirus (rice gall dwarf virus, RGDV) directly binds the Dome receptor’s extracellular domain, triggering receptor dimerization and JAK/STAT activation. Structural and mutational analyses pinpoint cysteine 743 in Dome as essential for viral recognition, establishing Dome as the first identified viral pattern recognition receptor (PRR) in insects capable of initiating JAK/STAT signaling, a pathway previously thought to be exclusively cytokine dependent. Furthermore, we identify viperin as a transcriptional factor STAT-regulated antiviral effector with broad-spectrum activity against multiple rice viruses. Intriguingly, RGDV’s nonstructural protein Pns11 competitively binds STAT, blocking its phosphorylation by JAK and nuclear translocation, thereby suppressing viperin expression. These findings elucidate how leafhopper Dome functions as a viral PRR and how arboviruses antagonize Dome-JAK-STAT signaling to promote persistent viral infection. [Display omitted] •Viral infection activates Dome-JAK-STAT signaling pathway via P8-Dome recognition•STAT directly regulates antiviral viperin expression in leafhopper•Viperin against multiple arboviruses underscores its importance in insect immunity•RGDV Pns11 inhibits JAK/STAT signaling to enhance viral persistence Insect JAK/STAT signaling is crucial for antiviral defense, yet its activation by arboviruses is unclear. Chen et al. reveal that RGDV uses its outer capsid protein P8 to activate the Dome receptor, initiating JAK/STAT signaling and viperin expression, while the virus inhibits this response via its protein Pns11.